Classroom Behaviour Management: The effects of in-service training on elementary teachers’ self-efficacy beliefs - Gaudreau, Nancy; Royer, Égide; Frenette, Éric; Beaumont, Claire; Flanagan, Tara (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2013)
We examined a training program in classroom management in relation to the efficacy beliefs of elementary school teachers. The training program used a quasi-experimental design with a waitlist control group. Twenty-seven elementary school teachers in the greater Quebec City area participated. The repeated measures ANOVA results revealed positive effect of the program on teachers’ personal teaching efficacy beliefs, and in the teachers’ perceived self-efficacy in managing difficult behaviours in the classroom. A group by time interaction effect was also observed with regard to the teachers’ perceived self-efficacy in eliciting principals’ support where participating teachers were more confident in their interactions with principals at follow-up. Factors that influence the development of self-efficacy beliefs of teachers and implications for practice are discussed.